A Descriptive Study of Feelings of Arrested Escape (Entrapment) and Arrested Anger in People Presenting to an Emergency Department Following an Episode of Self-Harm - Clarke, Martin; McEwan, Kirsten; Ness, Jennifer; Waters, Keith; Basran, Jaskaran; Gilbert, Paul (Frontiers in Psychiatry, 2016)
Background and objectives: To explore the role of elevated feelings of anger and desires to escape (fight/flight) which are experienced as inhibited, blocked and arrested (i.e. arrested anger and arrested flight/escape leading to feelings of entrapment). This descriptive study developed measures of arrested anger and arrested flight and explored these in the context of a recent self-harm event in people presenting to a Hospital’s Emergency Department (ED). Methods: Fifty-eight individuals presenting to an ED following an act of self-harm were recruited. Participants completed newly developed measures of arrested flight, arrested anger and anger with self in regard to self-harm and suicide intent and depression. Results: 93% participants presented after self-poisoning. The majority (95%) reported having experienced high escape motivation that felt blocked (arrested flight) with 69% reporting feeling angry with someone but unable to express it (arrested anger). For many participants (53.7%), strong desires to escape from current situations and/or to express anger did not diminish immediately after the act. Limitations: As with many studies, a select group of participants agreed to take part and we did not keep records of how many refused. There are no other validated measures of arrested escape and arrested anger and so for this study, our short item-focused measures rely on face validity. Conclusions: Arrested defences of fight and flight, and self-criticism are common in those who have self-harmed and may continue after acts of self-harm. Many participants revealed that talking about their experiences of escape motivation and blocked anger (using our measures) was helpful to them. Practice points: • Feelings of entrapment and arrested anger are common in people who self-harm • Clinicians could benefit from increased awareness and measures of arrested flight and arrested anger • Discussing these concepts and experiences appears to be useful to people who have self-harmed • Further research is needed on how best to help people with such experiences